2022
DOI: 10.1155/2022/9926635
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Qiliqiangxin against Doxorubicin-Induced Cardiomyopathy by Suppressing Excessive Autophagy and Apoptosis

Abstract: Background. Doxorubicin (DOX) is one of the most potent and widely prescribed antitumor agents; however, its clinical use is limited by cardiac side effects. In this study, we aimed to clarify the protective effects of Qiliqiangxin (QL), a traditional Chinese medicine formulation, on DOX-induced cardiotoxicity and to explore the underlying mechanisms in a rat model. Methods. Male Sprague-Dawley rats were randomly assigned to three groups with different interventions (control, DOX, and DOX plus QL) for 31 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…46 This is a signal that autophagic precursors germinate from the endoplasmic reticulum, accompanied by the formation of an initial complex composed of unc-51-like kinase 1, rb1-induced curl protein 1 and Atg. 47,48 The study demonstrated that DOX treatment increased the…”
Section: Discussionmentioning
confidence: 99%
“…46 This is a signal that autophagic precursors germinate from the endoplasmic reticulum, accompanied by the formation of an initial complex composed of unc-51-like kinase 1, rb1-induced curl protein 1 and Atg. 47,48 The study demonstrated that DOX treatment increased the…”
Section: Discussionmentioning
confidence: 99%
“…In normal and hypertrophic rat cardiomyocytes, QLQX inhibited I Ca,L , which may serve as one of the underlying mechanisms of its therapeutic effects [ 24 ]. A recent study investigated the protective effect of QLQX on doxorubicin-induced cardiotoxicity in a rat model [ 25 ]. Left ventricular remodeling is also alleviated by QLQX in rats with pressure overload-induced heart failure [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…DIC is a life-threatening progressive cardiomyopathy caused by DOX cardiotoxicity [ 97 ]. DOX is a chemotherapeutic drug for patients with malignant tumours.…”
Section: Dicmentioning
confidence: 99%